Comparing Empirical with Perceived Trends in Wildlife, Livestock, Human Population and Settlement Numbers in Pastoral Systems: The Greater Maasai Mara Ecosystem, Kenya - Kariuki, Juliet B.; Ogutu, Joseph O.; Kifugo, Shem C.; Senteu, Jully S.; Ojwang, Gordon; Olff, Han (International Livestock Research Institute, 2021)
Human activities are driving wildlife population declines worldwide. However, empirical understandings of their operation and consequences for wildlife populations and habitats are limited. We explored relationships between empirical and perceived wildlife and livestock population trends in Kenya using data on i) aerial monitoring of wildlife and livestock populations during 1977-2018, ii) human population censuses; and iii) semi-structured interviews with 338 male and female respondents from 250 households from four zones of the Greater Maasai Mara Ecosystem in 2019 and 2020. Wildlife numbers declined by 72.3% but sheep and goats increased by 306.4%. Yet nearly 50% of the interviewees perceived increases in wildlife numbers during 2011-2020 but concurrent decreases in livestock numbers because wildlife compete with livestock for resources. About one third of the respondents perceived an increase in the number of people living within conservancies and around the reserve and considered this indicative of a developing and thriving community. Notable discrepancies between the empirical and perceived trends were often more apparent than real and collectively suggest that incentives that promote wildlife are evidently viewed as less attractive than those that encourage increasing human and livestock numbers. Reconciling such apparent contradictions in empirical and perceived patterns is essential to extracting insights for formulating policies for sustaining livestock and wildlife populations and their habitats while promoting human welfare in grasslands.